2010
DOI: 10.1002/jsfa.3959
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties, radical scavenging activity and biomolecule protection capacity of flavonoid naringenin and its glycoside naringin: a comparative study

Abstract: The data obtained support the importance of characterizing the ratio naringin/naringenin in foods when they are evaluated for their health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
175
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(203 citation statements)
references
References 41 publications
12
175
0
3
Order By: Relevance
“…8) A study has shown that glycosylation attenuated the efficiency in inhibiting the xanthine oxidase enzyme and that the aglycone acted as an active chelator of metallic ions. 9) However, to the best of our knowledge, the preventive effect of dietary kaempferol glycoside and its aglycone on diabetes in (type 2) model mice KK-A y has not previously been reported.…”
mentioning
confidence: 89%
“…8) A study has shown that glycosylation attenuated the efficiency in inhibiting the xanthine oxidase enzyme and that the aglycone acted as an active chelator of metallic ions. 9) However, to the best of our knowledge, the preventive effect of dietary kaempferol glycoside and its aglycone on diabetes in (type 2) model mice KK-A y has not previously been reported.…”
mentioning
confidence: 89%
“…These compounds are present in many sources, including citrus fruits [7] [8] [9] [10] [11]. The therapeutic or even toxic activity, e.g., antioxidant, anti-inflammatory, antibacterial, antimutagenic, antiviral and antimetastatic effects, has been reported in a great number of these flavonoids [12] [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…These results provide important information about the structure-activity relationship of various natural flavanones in potentiating BK Ca channels, and guide future studies for identifying and modifying flavanone compounds. As suggested by a previous study (Saponara et al, 2006), it is encouraging to find that naringenin, a predominant flavanone in grapefruit, shows an appreciable potentiation of BK Ca channel activity because the beneficial effects of this compound are well recognized as an antioxidant, a free radical scavenger, and an immune modulator Du et al, 2009;Cavia-Saiz et al, 2010;Yilma et al, 2013).…”
Section: Discussionmentioning
confidence: 73%